Global financial crisis: Implications for trade and industrial restructuring in India - Prabir De; Chiranjib Neogi (Asian Development Bank Institute (ADBI), 2011)
This study investigates the impact of global crisis shocks on India's trade and industry. We use both panel data modeling and vector autoregression techniques to understand the dynamic effects of global crisis shocks on Indian industry and trade. The estimated results of panel data models show that changes in trade composition are positively associated with changes in manufacturing composition in India, controlling for other variables. However, there is no strong indication that Indian industry has been severely harmed by the fall in demand in crisis-affected advanced economies such as the United States (US), the European Union (EU), and Japan, holding other things constant. Since there may be lags between changes in composition in export and industry, the study then explores the dynamic effects of global crisis shocks on Indian industry and trade with the help of vector autoregression techniques. The findings of the study indicate that the compositional change in industry has responded significantly to exports to the US, Japan, and the EU in the crisis period. Variance decomposition of compositional change in industry reveals that during the pre-crisis period, almost 100% of the variation in compositional change in industry depended on its own variation, while in the crisis period about 20% of the variation in compositional change in industry has depended on the exports to the EU, Japan, and the US. Therefore, the effect of global crisis shocks of India's exports to advanced economies during the crisis period has been transmitted to Indian industry. However, Indian industry has not responded significantly to the shocks of imports from the advanced economies, while the response to its own shocks is significant during both pre- and postcrisis periods. The study also indicates that India's trade openness has responded mildly to the shock of exports to the US. India's trade with the US, coupled with US GDP, has significantly contributed to the variability of India's trade openness in the crisis period, accounting for 40% of the variation of the trade-GDP ratio of India, whereas India's trade with the EU and Japan has had either no effect or very insignificant effect on India's trade openness. This study suggests that Indian industry has not been significantly harmed by the ongoing global crisis. Even though India continues to enjoy relatively large domestic demand, the compositional change (positive) in the manufacturing sector would decrease if the crisis continues, resulting in a slowdown in growth and a rise in stagnation.
Keywords: F02; F13; F17; F42; F47; L6; L7; 330; Wirtschaftskrise; Weltkonjunktur; Finanzmarktkrise; Makroökonomischer Einfluss; Außenhandelseffekt; Industriekonjunktur; Indien